-3n+30=-6(6+6n)

Simple and best practice solution for -3n+30=-6(6+6n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3n+30=-6(6+6n) equation:


Simplifying
-3n + 30 = -6(6 + 6n)

Reorder the terms:
30 + -3n = -6(6 + 6n)
30 + -3n = (6 * -6 + 6n * -6)
30 + -3n = (-36 + -36n)

Solving
30 + -3n = -36 + -36n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '36n' to each side of the equation.
30 + -3n + 36n = -36 + -36n + 36n

Combine like terms: -3n + 36n = 33n
30 + 33n = -36 + -36n + 36n

Combine like terms: -36n + 36n = 0
30 + 33n = -36 + 0
30 + 33n = -36

Add '-30' to each side of the equation.
30 + -30 + 33n = -36 + -30

Combine like terms: 30 + -30 = 0
0 + 33n = -36 + -30
33n = -36 + -30

Combine like terms: -36 + -30 = -66
33n = -66

Divide each side by '33'.
n = -2

Simplifying
n = -2

See similar equations:

| 3x^3+25=x^2+75 | | 13=3n+6-8 | | 8b-12b+10b= | | x^2+3x-72=4x | | 9l=3l+3m | | 0.66X-16=0 | | 6(w-1)=3(w+5) | | 26-5x=-7(x-4) | | (-8y-5)(7y)*y=-3 | | 5p+2=11+4p | | 57=-7(7b-3)-(7-6b) | | 6x+6=3x | | 26-5x=-7-3r | | 4(u-4)-6u=4 | | 20-4(2w+1)=6w-4(6+w) | | (-8y-5)(7y)y=-3 | | 8c-3d=6 | | 1d+8=2d-17 | | 0.7m+0.3m=2m-4 | | p=m+k+n | | -6(x-3)-4(6-6x)=12 | | -6-3(6+4x)=-24-2x | | 91=-7(2n-7) | | -5*(1/9+x)=0 | | 114=(x+2)15-3x | | -(4y+3z-4)= | | x+1(2)+x(2)=14 | | 2x+8=8+2x | | 18=c+5/2 | | (x+2)(x-1)(x+1)=0 | | -5a+2a=12-15 | | 15-2(2w+1)=7w-2(7+w) |

Equations solver categories